Penguatan Empati dan Literasi Psikologi Masyarakat Melalui Bedah Buku Psikologi Anak Jalanan - Ecep Supriatna; Wahyu Aulizalsini A; Ferdy Muzzamil; Lenny Utama Afriyenti (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2025)
This Community Service Program (PKM) was initiated in response to the low level of public literacy in psychology regarding the psychosocial conditions of street children, particularly in relation to emotional development, parenting patterns, and the impact of traumatic experiences. The objective of this program was to enhance participants’ understanding, empathy, and humanistic attitudes toward the psychological dynamics of street children as a vulnerable group. The program was implemented through a hybrid book review activity of Psychology of Street Children, involving the book’s author, psychologists, and academics as resource persons. This method was integrated with the presentation of developmental psychology theories, interactive discussions, and case analyses of street children. The main materials were based on Ecological Systems Theory, Attachment Theory, chronic stress, negative self-concept, and resilience to explain the influence of family systems, social environments, and structural factors on the behavior and development of street children. The results of the program indicate an improvement in participants’ understanding, as reflected in their ability to identify ecological and psychosocial factors affecting street children, as well as a shift in attitudes toward greater empathy and reduced stigmatization. The implications of this program underscore the importance of a multidisciplinary approach to addressing the needs of street children through emotional support, psychosocial assistance, and creative interventions, and serve as a foundation for the development of comprehensive and sustainable support programs that bridge academic literature with community educational needs.ABSTRAKKegiatan Pengabdian kepada Masyarakat (PKM) ini dilatarbelakangi oleh rendahnya literasi psikologi masyarakat mengenai kondisi psikososial anak jalanan, khususnya terkait perkembangan emosional, pola pengasuhan, dan dampak pengalaman traumatis. Tujuan kegiatan ini adalah meningkatkan pemahaman, empati, dan sikap humanis peserta terhadap dinamika psikologis anak jalanan sebagai kelompok rentan. Metode pelaksanaan PKM dilakukan melalui kegiatan bedah buku Psikologi Anak Jalanan secara hybrid yang melibatkan penulis buku, psikolog, dan akademisi sebagai narasumber. Metode ini dikombinasikan dengan pemaparan teori psikologi perkembangan, diskusi interaktif, dan analisis kasus anak jalanan. Materi utama mengacu pada Teori Ecological Systems, Attachment Theory, stres kronis, konsep diri negatif, dan resilience untuk menjelaskan pengaruh sistem keluarga, lingkungan sosial, serta faktor struktural terhadap perilaku dan perkembangan anak jalanan. Hasil kegiatan menunjukkan peningkatan pemahaman peserta yang tercermin dari kemampuan mengidentifikasi faktor ekologis dan psikososial yang memengaruhi anak jalanan, serta adanya perubahan sikap peserta menjadi lebih empatik dan tidak stigmatis terhadap anak jalanan. Implikasi kegiatan ini menegaskan pentingnya pendekatan multidisipliner dalam penanganan anak jalanan melalui dukungan emosional, pendampingan psikososial, dan intervensi kreatif, serta menjadi dasar bagi pengembangan program pendampingan yang komprehensif dan berkelanjutan yang menjembatani literatur akademik dengan kebutuhan edukasi masyarakat.